Self-Reported Depression and Its Relationship with Socio-Demographic Characteristics among Medical Students - Allah Bachayo Rajar, Naseem Aslam Channa, Muhammad Hanif Mugheri (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: In Pakistan, among various cities, the rate of depression is reported to be between 60–70% among medical students. This study was performed to estimate the prevalence of depression and its factors among medical students at Muhammad Medical College, MirpurKhas, Sindh, Pakistan. Methods: A cross-sectional study was performed at Muhammad Medical College MirpurKhas, Sindh. The study tool was a semitortured questionnaire comprising of sociodemographic questions and depression, anxiety, stress (DASS-42) self-reporting scale. Throughout the study, medical undergraduate students were hired using a random sample technique. The descriptive statistical analysis, i.e., mean, standard deviation, range, frequency, and percentages were calculated using SPSS version 26. Results: The frequency rate of male and female students was 49.5% and 50.5%, respectively. Of all the 34% of medical students who showed positive depression symptoms, 27% had mild, and 7% had moderate depression. Female students had a higher depression frequency. Concerning the factors of depression, the rural residence demonstrated a significantly negative association [0.24 (0.104-0.574)], but living in a shared room showed a non-significantly positive association [OR 2.78 (0.501-15.46)] with depression among medical students. A monthly expense of 20000 PKR revealed a non-significantly positive association [1.078 (0.409-2.84)] with depression. In addition, parental level of education showed a significant association (P<0.005) with depression. Conclusion: Female students has high frequency of depression than male students. The depression factors among medical students were found to be financial, parental education, and living in shared room. So, the appropriate policies should be implemented to reduce the burden of disease. Keywords: Frequency of depression, DASS-42 scale, Factors of Depression, Medical students.